A COMPARATIVE STUDY ON THE QUALITY OF DIFFERENT OLMESARTAN TABLETS AVAILABLE IN THE ALBANIAN MARKET - Basha, Brunilda; Malaj, Ledjan; Myftari, Elton (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Olmesartan (OLM) is the latest molecule of registered and marketed in Albania for the treatment of arterial hypertension. This study aims to carry out a quality control (QC) test on all the alternatives available in the Albanian market and evaluate if there are any outstanding differences terms of quality as it is in terms of price. Methods: There were carried out various QC pharmacopeias tests on a range of different productions of OLM 20 mg tablets. There have been carried out weight variation test, setting the diameter, thickness, friability, hardness, disintegration, and dissolution test. The pharmaceutical equivalents were compared to the reference product in terms of similar dissolution factor (f ) of dissolution profiles and the dissolution efficiency. The dissolution test was carried out using Varian dissolution apparatus 2 (50 rpm, 37Â±0.5Â°C); Varian Prostar high-performance liquid chromatography was used to determine the OLM concentration at wavelength 250 nm; Varian hardness VK 200, Guoming BJ-2 disintegration apparatus were used for the respective tests. 2 Results: The study showed that although there is a consistent difference in market price, their quality is comparable. The dissolution profiles were very similar. All formulations met the standards of the United States Pharmacopoeia. Conclusion: All tablets were within the pharmacopoeia limits. The present study confirmed that the difference in price not always represents a difference in terms of quality. Keywords: Olmesartan medoxomil, Quality control, Pharmacopoeia standards.